Gdy spotykają się różne kultury. Oblicza dzieciństwa na emigracji na przykładzie Norwegii - Katarzyna Jakubowska (Problemy Wczesnej Edukacji)
The aim of this text is an attempt to show different perspectives of the aspect of childhood spent as an emigrant, in this case in Norway. The stereotype describing this Scandinavian country as not very different culturally from Poland is a subject worth going into more deeply. Childhood spent outside the home country may have different faces. This article shows both the aspect of cultural differences and expectations connected with emigration and also brings the reader to a place in which he or she may objectively find out whether the common opinion on the ease of children’s integration into the culture of another country is misleading or not.